Phase II Trial Using a Combination of Oxaliplatin, Capecitabine, and Celecoxib with Concurrent Radiation for Newly Diagnosed Resectable Rectal Cancer - Araujo‐Mino, Emilio P.; Patt, Yehuda Z.; Murray‐Krezan, Cristina; Hanson, Joshua A.; Bansal, Pranshu; Liem, Ben J.; Rajput, Ashwani; Fekrazad, M. Houman; Heywood, Glenory; Lee, Fa Chyi (The oncologist (Dayton, Ohio), 2018)
Lessons Learned Colorectal cancers exhibit a high level of cyclooxygenase‐2 (COX‐2) expression with strong preclinical rationale for improved clinical outcomes with COX‐2 inhibition. Celecoxib is a COX‐2 inhibitor and we have shown that it can be safely combined with capecitabine and oxaliplatin as part of neoadjuvant treatment with radiation therapy (RT) in rectal cancer. There was a significant improvement in skin toxicity with this combination as compared with historical data. Considering the field has moved on to single‐agent capecitabine, we believe future trials with capecitabine and celecoxib hold potential. Background Improved survival is seen among patients with rectal cancer who achieve pathologic complete response (pCR) after neoadjuvant therapy. Cyclooxygenase‐2 (COX‐2) expression is increased in gastrointestinal malignancies and it may serve as a target to enhance pathologic response. A trial combining chemoradiation and COX‐2 inhibition was conducted to evaluate the pCR rate, surgical outcomes, survival, and treatment toxicity. Methods Patients with resectable (T3‐4, N1‐2) rectal cancer within 12 cm of the anal verge were included in this phase II clinical trial. The neoadjuvant treatment consisted of capecitabine 850 mg/m2 b.i.d. Monday through Friday for 5 weeks, weekly oxaliplatin 50 mg/m2 intravenous (IV), celecoxib 200 mg b.i.d. daily, along with concurrent 45 gray radiation therapy in 25 fractions. Results Thirty‐two patients were included in the final analysis. The primary endpoint was pCR: 31% (95% confidence interval [CI]: 16%–50%). Secondary endpoints were surgical downstaging (SD): 75% (95% CI: 57%–89%) and sphincter‐sparing surgery (SSS): 56% (95% CI: 38%–74%). Common grade >3 toxicities were diarrhea and abnormal liver function tests (9% each). Grade 0 and 1 toxicities included radiation dermatitis (59% and 34%, respectively) and proctitis (63% and 28%, respectively). At 3 years, disease‐free survival and overall survival (OS) were 84% (95% CI: 65%–93%) and 94% (95% CI: 77%–98%), respectively. Conclusion Chemoradiation with celecoxib in rectal cancer was well tolerated and demonstrated high rates of pCR, SD, and SSS. Improvement in skin toxicity (34% grade 1 and no grade 3/4) as compared with historical results (43%–78% grade 3/4) seems to be a significant improvement with addition of celecoxib to neoadjuvant chemotherapy. 经验总结 • 结直肠癌具有高环氧合酶‐2（COX‐2）表达水平, 存在强有力的临床前证据表明, 抑制COX‐2表达可改善结直肠癌的临床结局。塞来昔布是COX‐2抑制剂, 已有研究证实塞来昔布可以安全地联合卡培他滨与奥沙利铂作为新辅助治疗的一部分, 联合放疗用于治疗直肠癌。 • 与历史数据相比, 使用这一联合疗法治疗后皮肤毒性获得显著改善。考虑到肿瘤治疗领域已经转移到卡培他滨单药治疗, 我们相信将来可能开展关于卡培他滨和塞来昔布的试验。 摘要 背景.接受新辅助治疗后达到病理完全缓解（pCR）的直肠癌患者的生存期获得改善。胃肠道恶性肿瘤患者的环氧合酶‐2（COX‐2）表达水平较高, 而COX‐2可作为提高病理缓解率的靶点。我们开展了一项联合使用放化疗与COX‐2抑制剂的研究, 以评价pCR率、手术结局、生存期和治疗毒性。 方法.本项II期临床试验纳入了痔环在12cm以内的可切除（T3‐4, N1‐2）直肠癌患者。新辅助疗法包括卡培他滨850 mg/m2 b.i.d., 周一到周五给药, 共5周, 奥沙利铂50 mg/m2每周静脉内（IV）给药, 塞来昔布200 mg b.i.d.每日给药, 同时进行同步放疗（45Gy/25次）。 结果.32例患者被纳入最终分析。主要终点为pCR：31%[95%置信区间(CI)：16%–50%]。次要终点为手术降级（SD）：75%（95% CI：57%–89%）和保留括约肌手术（SSS）：56%（95% CI：38%–74%）。常见的>3级毒性为腹泻和肝功能检查异常（各9%）。0级和1级毒性包括放射性皮炎（分别为59%和34%）和直肠炎（分别为63%和28%）。3年时的无病生存率和总生存率（OS）分别为84%（95% CI：65%–93%）和94%（95% CI：77%–98%）。 结论.使用塞来昔布对直肠癌患者进行放化疗可良好耐受, 并且pCR、SD和SSS率均较高。与历史结果（3/4级：43%–78%）相比, 在新辅助化疗中添加塞来昔布可显著改善皮肤毒性（1级：34%；3/4级：无）。